Effectiveness of Pandan Leaf Decoction on Sleep Quality among Nursing Students - Amala, Riztia Nur; Sulastri, Afianti; Sumartini, Sri (Jurnal Kesehatan, 2025)
Nursing students are a productive population that often experiences sleep disturbances triggered by academic pressure, social demands, and emotional stress. When left unmanaged, sleep problems can impair concentration, academic achievement, and overall mental well-being. Pandan leaves contain various bioactive constituents, including flavonoids, alkaloids, tannins, saponins, and 2-acetyl-1-pyrroline, which may provide calming and sedative effects that support better sleep. This study aimed to examine the effectiveness of pandan leaf decoction in improving sleep quality among nursing students. A pre-experimental one-group pretest–posttest design was used with 30 students from the Indonesian University of Education, selected via quota sampling. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI). Prior to the intervention, 83.3% of participants exhibited poor sleep quality with a mean PSQI score of 7.23. After consuming the pandan leaf decoction for 14 days, 73.3% of participants shifted into the good sleep category, yielding a reduced mean posttest score of 4.73. A paired sample t-test indicated a significant improvement in sleep quality (p=0.000; p<0.05). These findings show that pandan leaf decoction can help improve sleep quality among nursing students. As a safe and natural herbal option, it may be recommended as a complementary strategy to support holistic nursing care for managing sleep disturbances.